Exploring the potential of in-situ foam 3D printing: Effects of printing parameters and the development of functionally graded foams - Viktória Kunsági; Péter Széplaki; Márton Tomin (eXPRESS Polymer Letters)
In this study, we investigated the influence of processing parameters on the cellular structure and density of specimens fabricated using in-situ foam 3D printing. First, we conducted a comprehensive analysis to examine how the combined effects of printing temperature and speed influence the four key stages of the foaming process: gas dissolution, cell nucleation, cell growth, and stabilization. By evaluating the structural characteristics of the printed foams, we identified the dominant mechanisms governing each stage. Next, we explored the effect of nozzle diameter, an aspect previously unexamined in the literature. We found that smaller nozzle diameters promote higher cell density due to enhanced pressure drop and shear-induced nucleation, resulting in a 36.78% reduction in density and a 60.31% increase in cell density when using a 0.4 mm nozzle instead of 0.8 mm (at 240°C, 60 mm/sec). Finally, we fabricated functionally graded four-layer structures by adjusting the printing temperature for each layer to control porosity distribution. To evaluate the mechanical performance of these graded structures, we performed three-point bending and drop-weight impact tests, allowing us to assess how layer order influences mechanical properties. Our results showed that proper layer sequencing can increase flexural strength by up to 69.35% and improve perforation energy by more than 94.82% compared to homogeneous structures.